Pushing the boundaries: an interview with Dae-Hyun Kim on terahertz devices - Defu Wang (National Science Review, 2024)
III–V compound semiconductors, such as InGaAs/InAlAs, exhibit exceptional carrier transport properties, establishing them as fundamental elements in terahertz (THz) applications crucial for the development of 6G networks. These materials present the potential for high-performance, energy-efficient THz devices. Furthermore, their compatibility with heterojunction integration, particularly in hetero-integration with silicon-germanium (SiGe) bipolar complementary metal–oxide–semiconductor (BiCMOS), paves the way for cutting-edge THz devices. This advantage highlights the crucial role of III–V semiconductors in driving THz and 6G technology, meeting the evolving demands of future wireless communication and sensing systems. NSR conducted an interview with Dr. Dae-Hyun Kim, a semiconductor expert with a distinguished academic and professional background. Dr. Kim embarked on his career at Teledyne Scientific Company in 2008, later joining SEMATECH in 2012, where he played a crucial role in propelling semiconductor technology forward. In 2015, he assumed the position of an Associate Professor at Kyungpook National University. Dr. Kim's journey embodies his long commitment to the field, underscored by his remarkable contributions. In this interview, Dr. Kim shared his insights on fostering collaboration within the semiconductor field. He particularly emphasized on effective approaches for advancing research and innovation in semiconductor technology.